Severe dengue in travellers: pathogenesis, risk and clinical management - Halstead, Scott; Wilder-Smith, Annelies (Journal of travel medicine, 2019)
AbstractRationale for review. Dengue is a frequent cause of febrile illness among travellers and has overtaken malaria as the leading cause of febrile illness
Gesehen am 04.12.2019